INNOVATIVE APPROACHES TO THE VALIDATION OF ANALYTICAL METHODS IN PHARMACEUTICAL MANUFACTURING - Kustovska , Antonina; Maksymiuk , Mariia; Rudenko, Vira; Yefymenko, Valerii; Levchenko, Serhii (Science-based technologies, 2025)
Modern pharmaceutical manufacturing requires ongoing advancement of analytical quality control methods, which play a central role in ensuring the efficacy, safety, stability, and reproducibility of pharmaceutical products. The urgency of improving validation strategies stems from increasing demands by global regulatory agencies such as the FDA and EMA, as well as the need for compliance with GMP and ICH standards. In this context, innovative approaches to analytical method validation, particularly the implementation of Quality by Design (QbD) and Process Analytical Technology (PAT), have emerged as vital tools for systematic and science-driven development of robust methods. The article formulates the problem of enhancing traditional validation frameworks that rely heavily on empirical practices and often neglect the identification and control of critical method attributes (CMA) and critical process parameters (CPP). As a solution, the adoption of Design of Experiments (DoE) methodology is proposed to support the construction of a method design space, optimization of analytical conditions, and assessment of the influence of multiple variables. The article analyzes real-world examples of successful QbD, PAT, and DoE application in the validation of methods used in pharmaceutical substance manufacturing and finished dosage forms. It demonstrates how mathematical modeling and response surface methodology (RS) can be applied to visualize relationships between variables and determine ideal analytical settings. The conclusions highlight the strategic advantages of incorporating innovative validation approaches, including improved method robustness, reliability, and alignment with modern regulatory expectations. The findings serve as a valuable contribution to the development of more effective quality assurance systems in pharmaceutical enterprises, particularly within evolving regulatory and technological landscapes.